The Effect of Product Quality and Product Price Towards Customer Satisfaction at Blackcup Coffee and Roaster - Varelyo Ayrton Mickinen Poluan; S. L. H. V. J. Lapian; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: The purpose of this study is to determine the effect of product quality and product price towards customer satisfaction at blackcup coffee and roaster Manado. The population on this study consist of people who hanging out at blackcup coffee and roaster Manado, which the value is unknown. The sample for this study is 100 respondents. The sampling technique used is a purposive sampling method and the data collection method is in the form of a questionnaire that is run through Google Form. Furthermore, testing and data analysis was carried out using SPSS 28 software. Keywords: product quality, product price, customer satisfaction